Stepwise growth of melamine-based dendrimers onto carbon fibers and the effects on interfacial properties of epoxy composites. (18th January 2017) - Zhao, Min; Meng, Linghui; Ma, Lichun; Wu, Guangshun; Xie, Fei; Ma, Lina; Wang, Wei; Jiang, Bo; Huang, Yudong
Abstract: A practical method for growing generation 1–3 melamine-based dendrimers onto carbon fibers (CFs) surface was proposed. The microstructures and interfacial properties of CFs before and after modification were investigated. X-ray photoelectron spectroscopy (XPS) confirmed the successful growth of different generation dendrimers. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) images showed that melamine-based dendrimers grafting enhanced surface roughness, and this effect was more pronounced with increasing generation. The results of dynamic contact angle (DCA) demonstrated that the surface energy and the wettability of the grafted CFs were increased with generation. After generation 3 dendrimers grafting, the interfacial shear strength (IFSS) and impact strength of CF/epoxy composites were enhanced by 61.8% and 39.9%, respectively. The tensile strength of the composites were enhanced as the generation increased. Moreover, the reinforcing and toughening mechanisms were also discussed.